The Relationship of Corporate Governance and Profitability with Corporate Social Responsibility Disclosure in Pakistan - Saleem, Dr Faiza; Shehla Gul Afridi; Kamran Ahmed (Journal of Business & Tourism, 2023)
The objective of this research study is to investigate the impact of corporate governance attributes and profitability on corporate social responsibility disclosure (CSRD) among listed non-financial firms in Pakistan. The current study gathered data from the published annual reports of the 66 non-financial firms listed on the Pakistan Stock Exchange (PSX) from 2013 to 2016. The study employed a fixed effect model or a random effect model for data analysis, along with some pre-requisite diagnostic tests. The results of the study demonstrate the following outcomes: First, the board size, managerial ownership, and return on assets are positively linked with corporate social responsibility disclosure; second, return on equity shows a significant negative relationship with corporate social responsibility disclosure. Importantly, this study suggests that corporate governance attributes and firm profitability are the most significant components in improving corporate social responsibility disclosure. The research study has some important implications for academicians, auditors, and policymakers in improving corporate social responsibility reporting disclosure.